Learning while doing: program evaluation of the Medical Library Association Systematic Review Project. - Boden, Catherine; Ascher, Marie T.; Eldredge, Jonathan D. (Journal of the Medical Library Association)
Objectives: The Medical Library Association (MLA) Systematic Review Project aims to conduct systematic reviews to identify the state of knowledge and research gaps for fifteen top-ranked questions in the profession. In 2013, fifteen volunteer-driven teams were recruited to conduct the systematic reviews. The authors investigated the experiences of participants in this large-scale, volunteer-driven approach to answering priority research questions and fostering professional growth among health sciences librarians. Methods: A program evaluation was conducted by inviting MLA Systematic Review Project team members to complete an eleven-item online survey. Multiple-choice and short-answer questions elicited experiences about outputs, successes and challenges, lessons learned, and future directions. Participants were recruited by email, and responses were collected over a two-week period beginning at the end of January 2016. Results: Eighty (8 team leaders, 72 team members) of 198 potential respondents completed the survey. Eighty-four percent of respondents indicated that the MLA Systematic Review Project should be repeated in the future and were interested in participating in another systematic review. Team outputs included journal articles, conference presentations or posters, and sharing via social media. Thematic analysis of the shortanswer questions yielded five broad themes: learning and experience, interpersonal (networking), teamwork, outcomes, and barriers. Discussion: A large-scale, volunteer-driven approach to performing systematic reviews shows promise as a model for answering key questions in the profession and demonstrates the value of experiential learning for acquiring synthesis review skills and knowledge. Our project evaluation provides recommendations to optimize this approach.